Tinjauan Hukum Undang-Undang Investasi: Strategi Mendorong Pertumbuhan Ekonomi - Rahmawati; Putri, Kezia Hera; Fitriani, Adila; Pamungkas, Bagas; Siswajanthy S.H.,M.H., Farahdinny (Sharia Journal and Education Center Publishing, 2024)
Abstract This study aims to examine the role of investment in driving economic growth and assess effective strategies to increase investment in various sectors. In an ever-evolving economic era, investment is one of the important pillars in strengthening a country's economic base. This review includes an analysis of various investment methods, including foreign direct investment (FDI), infrastructure development, and human resource development. Using empirical data and case studies, this research concludes that a comprehensive and integrated approach such as strengthening pro-business policies, simplifying regulations, and improving the quality of education is crucial to creating a favorable investment environment. The findings of this research are expected to provide guidance for policymakers and stakeholders in designing more effective strategies to promote economic growth through increasedinvestment: A Strategy to Drive Economic Growth.